2014
DOI: 10.4314/thrb.v16i4.4
|View full text |Cite
|
Sign up to set email alerts
|

Injury outcome among helmeted and non-helmeted motorcycle riders and passengers at a tertiary care hospital in north-western Tanzania

Abstract: Motorcycle helmets have been reported to reduce the risk of death and head injuries following motorcycle accidents. The aim of this descriptive prospective study was to determine the injury outcome among helmeted and non-helmeted motorcyclists and passengers at a tertiary hospital in north-western Tanzania. A total of 654 patients involved in the motorcycle accident were studied. Of these, 468 (71.6%) were motorcyclists (riders) and the remaining 186 (28.4%) were passengers. The median age of patients at prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
4
8
0
Order By: Relevance
“…In this study, the mean age of victims was 35.6(12.7) years for cases and 36.7(12.1) years for controls. This founding is in line with previous studies, which found that the age of subjects involved in road crashes ranged from 25 to 35 years old and up to 38 years old (Tumwesigye et al 2016 ; Brown et al 2011 ; Tidjani et al 2018 ; Hode et al 2017 ; Lam et al 2019 ; Xiong et al 2016 ; Chalya et al 2014 ). As in our study, some previous studies did not found age associated with head injuries (Orsi et al 2014 ; Lam et al 2020 ; Walle et al 2018 ; Kamulegeya et al 2015 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the mean age of victims was 35.6(12.7) years for cases and 36.7(12.1) years for controls. This founding is in line with previous studies, which found that the age of subjects involved in road crashes ranged from 25 to 35 years old and up to 38 years old (Tumwesigye et al 2016 ; Brown et al 2011 ; Tidjani et al 2018 ; Hode et al 2017 ; Lam et al 2019 ; Xiong et al 2016 ; Chalya et al 2014 ). As in our study, some previous studies did not found age associated with head injuries (Orsi et al 2014 ; Lam et al 2020 ; Walle et al 2018 ; Kamulegeya et al 2015 ).…”
Section: Discussionsupporting
confidence: 90%
“…Brown et al and Phillips et al observed in the USA that different lesions with intracranial trauma were significantly more present in subjects not wearing a helmet than in those who did (Brown et al 2011 ; Phillips et al 2017 ). For other authors, there was a relationship between injury severity (AIS) and helmet use (Baru et al 2019 ; Lam et al 2019 ; Xiong et al 2016 ; Chalya et al 2014 ), and not wearing a helmet would increase the risk of sustaining road traffic injuries (Tumwesigye et al 2016 ) or the risk of death from road crashes among motorcyclists (Chang et al 2016 ; Boniface et al 2016 ). According to Lam et al, head injuries are more likely to be associated with the use of non-standard helmets (Lam et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The motorcycle riders in this study were relatively young, which is consistent with the ndings of the WHO and several authors who have pointed out that young people are most affected by road tra c injuries (1, (18,19,26). Tumwesigye et al also noted in Kampala, Uganda, that more than half of motorcycle taxi drivers, among both the cases and controls, were between 25 and 34 years old (7).…”
Section: Driver Characteristicssupporting
confidence: 90%
“…Brown et al and Phillips et al observed in the USA that different lesions with intracranial trauma were signi cantly more present in subjects not wearing a helmet than in those who did (14,32). For other authors, there was a relationship between injury severity (AIS) and helmet use (24)(25)(26)33), and not wearing a helmet would increase the risk of sustaining road tra c injuries (7) or the risk of death from road accidents among motorcyclists (34,35).…”
Section: Factors Associated With Head Injuriesmentioning
confidence: 99%
“…Alcohol use has been studied among various populations in eastern Africa and has specifically shown to be a risk factor for road traffic injuries (Benegal et al, 2009; Boniface et al, 2016; Chalya et al, 2014; Staton et al, 2017), violence, physical abuse, and suicidal ideation. However, there is a lack of research on the age of first use, cost, and alcohol availability and their association with high‐risk alcohol behavior.…”
mentioning
confidence: 99%